The Conceptual Dilemma of the One‐Electron Picture in Describing the Uniaxial Magnetism at Linear Coordination Sites. Issue 21 (7th May 2019) - Koo, Hyun‐Joo; Kasapbasi, Esra E.; Whitten, Jerry L.; Whangbo, Myung‐Hwan
Abstract : High‐spin Fe 2+, Fe + and Co 2+ ions at linear two‐coordination sites exhibit uniaxial magnetism. In the one‐electron picture, the uniaxial magnetism of the Fe 2+ ion is explained, while those of the Fe + and Co 2+ ions are not, if the d‐state split pattern is 1e < 2e < 1a. The opposite is true if the d‐state split pattern is 1a < 1e < 2e. We resolved this conceptual dilemma by evaluating the relative stabilities for the various L states of linear molecules (Fe L 2 ) 0, (Fe L 2 ) –, and (Co L 2 ) 0 with L = C(SiH3 )3 on the basis of first‐principles broken‐symmetry and configuration interaction calculations. In the first‐principles picture, the total energy of an electron configuration depends not only on the energy sequence of the occupied d‐states, as do the one‐electron picture, but also on the electron repulsion between occupied d‐states, which is neglected by the one‐electron picture. Abstract : High‐spin Fe 2+, Fe +, and Co 2+ ions at linear‐coordination sites exhibit uniaxial magnetism. The d‐state split pattern of 1e < 2e < 1a explains the uniaxial magnetism of the Fe 2+ ion, but not those of the Fe + and Co 2+ ions. The opposite is true for the d‐state split pattern of 1a < 1e < 2e. This conceptual dilemma was explored by first‐principles broken‐symmetry and configuration interaction calculations.